Diagnostic Challenges of Quadricuspid Aortic Valve - A. Aragao, Roberto Cintra; Costa Cruz, Amanda Raquel; Machado Bispo, Iana Carine; Vahle, Vitor; Goncalves, Luiz Flavio Galvao; Barreto Filho , José Augusto Soares (International Journal of Medical Science and Clinical Research Studies, 2024)
The quadricuspid aortic valve (QAV) is a rare anatomical variation, and the estimated incidence is lower than 0,05% of all congenital heart diseases (1). It is usually found as an isolated alteration, however, it may be associated with other concomitant cardiac anomalies (2). In this case report, an atypical presentation of the QAV was observed, with a lot of clinical dissociation versus complementary exams of excellent accuracy for the diagnosis.